Identification of two previously unreported Duchenne muscular dystrophy gene variants in a patient diagnosed with a dystrophinopathy: a case report - Sarah Gerges; Rania Naoufal; Hicham Mansour (Journal of Medical Case Reports)
Abstract Introduction Duchenne muscular dystrophy and Becker muscular dystrophy are X-linked recessive disorders affecting muscle function, which are caused by mutations in the dystrophin gene (also known as the Duchenne muscular dystrophy gene). The resulting condition is dictated by the severity of the involved mutation; for instance, Duchenne muscular dystrophy presents in early childhood with rapid progression, whereas Becker muscular dystrophy exhibits a milder, later onset with slower progression. In this report, we present the case of a young patient with clinical symptoms of a dystrophinopathy, whose genetic analysis yielded two previously undescribed mutations within the dystrophin gene. Case presentation This paper focuses on a 12-year-old Syrian male patient with a 6-year history of progressive gait difficulty, lower limb weakness, and recurrent falls. Physical examination revealed a positive Gowers’ sign and pseudohypertrophy, but normal muscle strength. A diagnosis of myopathy was supported by elevated serum creatine kinase and a muscle biopsy showing dystrophic changes in the right quadriceps muscle. While the initial deletion and duplication screening in the Duchenne muscular dystrophy gene using multiplex ligation-dependent probe amplification was negative, further extensive genetic analysis revealed two novel hemizygous variants of uncertain significance in the Duchenne muscular dystrophy gene (c.536A > T p.(Asp179Val) and c.680C > T p.(Ser227Phe), with no other clinically relevant variants in the neuromuscular panel. Conclusion The identification of novel variants in the Duchenne muscular dystrophy gene, alongside the absence of pathogenic mutations in other genes investigated by the neuromuscular panel, strongly suggests an X-linked dystrophinopathy diagnosis in our patient. This case highlights the need for continued exploration of dystrophinopathies’ genetic variants. Further studies are required to elucidate the functional impact of these novel variants and to improve our understanding of the genotypic and phenotypic variability observed in these disorders, which may lead to a revolution in treatment approaches and potentially offer curative options for patients.